Integrating Naqli and Aqli Science in Islamic Education: Toward a Comprehensive Learning Model - Wawan Saepul Bahri; muhammad zuhdi; Suparto Suparto (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
In the context of globalization, Islamic education faces great challenges, especially related to secularization and separation between religious and general sciences. Therefore, it is very important to develop an educational system capable of combining spiritual and scientific aspects. Through this approach, Islamic education aims to form students' balanced character in intellectual, moral, and spiritual aspects, as well as prepare them to face the challenges of the times. For this reason, effective learning methods, such as mind mapping and blended learning, along with curriculum integration, need to be implemented to increase student engagement. Curriculum integration means combining general science and religion in one harmonized system. World knowledge is taught along with Islamic values, so that each subject helps to strengthen these values. For example, science is taught by paying attention to Islamic principles, so that there is no separation between world science and religion. However, the lack of facilities, qualified educators, and adequate funding for operations and development are the main challenges. In addition, the separation between religious science and general science, which separates the spiritual aspect from the worldly aspect, also contributes to the delay in Islamic education in keeping up with the development of science and technology. Therefore, an approach that unites religious and general science is important so that Islamic education remains relevant to the times and is able to face the challenges of globalization.